Pengaruh Persepsi Kemudahan dan Daya Tarik Iklan Terhadap Keputusan Menggunakan Dompet Digital “OVO” - Novi Aisha; Efry Kurnia (Bursa : Jurnal Ekonomi dan Bisnis, 2022)
and innovate. By accessing OVO, there are various perceptions of the convenience offered in the form of applications, such as payments, transfers, repurchases, and withdrawing funds. The development of the OVO digital wallet is also inseparable from the attractiveness of advertisements that are seen by the public, such as advertisements with attractive images about cashback and discounts and points that can be reused for transactions so that people think they can save expenses. This encourages people's desire to try or use the OVO application. The population in this study were students of the Muhammadiyah University of North Sumatra who used the OVO application. The sampling technique is probability sampling using proportionate stratified random sampling. proportionate stratified random sampling. The data collection technique used is a questionnaire. In this study, descriptive statistical analysis was used to describe the characteristics of the respondents who were the samples in the study. Data processing using SPSS software with data analysis techniques using multiple linear regression. The results showed that the perceived ease and attractiveness of advertising influenced the decision to use an ovo digital wallet.